Bioderived protoporphyrin IX incorporation into a metal-organic framework for enhanced photocatalytic degradation of chemical warfare agents. (June 2019) - Lee, Marilyn S.; Garibay, Sergio J.; Ploskonka, Ann M.; DeCoste, Jared B.
Abstract: Abstract : Porphyrins absorb light to initiate photocatalytic activity. The complex, asymmetric structures of natural porphyrins such as heme, chlorophyll, and their derivatives hold unique interest. A platform for biosynthesis of porphyrins in Escherichia coli is developed with the aim of producing a variety of porphyrins for examining their photocatalytic properties within a porous material. Bioderived protoporphyrin IX is tethered inside the highly porous metal-organic framework (MOF) NU-1000 via solvent-assisted ligand incorporation. This MOF catalyzes the photocatalytic oxidation of 2-chloroethyl ethyl sulfide with improved performance over an expanded range of the visible spectrum when compared to unmodified NU-1000.